2016
DOI: 10.1007/s00340-016-6563-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultracold metastable helium: Ramsey fringes and atom interferometry

Abstract: equation cannot be solved exactly. Level energies are therefore more difficult to calculate than for atomic hydrogen showing a more stringent test of atomic physics theory. Calculations of level energies and transition frequencies have pushed our understanding of atomic physics since the twenties of last century. A major breakthrough occurred in the nineties with the advent of variational calculations in a double basis set in correlated form for the electrons, adding relativistic and quantum electrodynamics (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We finally turn to the question of experimental observability of Fano coherences. We suggest metastable He(2 3 S 1 ) atoms [49,50] as a readily realizable Λ-system, in which to observe noise-induced coherent dynamics. The Λ-system is formed by the m = ±1 Zeeman sublevels of the metastable 3 S state and the nondegenerate excited 3 P 0 state as shown in Fig.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…We finally turn to the question of experimental observability of Fano coherences. We suggest metastable He(2 3 S 1 ) atoms [49,50] as a readily realizable Λ-system, in which to observe noise-induced coherent dynamics. The Λ-system is formed by the m = ±1 Zeeman sublevels of the metastable 3 S state and the nondegenerate excited 3 P 0 state as shown in Fig.…”
mentioning
confidence: 98%
“…As in the case of isotropic incoherent excitation considered above, the coherences exhibit quantum beats with frequency ∆ and lifetime 1/(Qr). The coherent evolution could be probed by applying a π/2 radiofrequency pulse (as part of the standard Ramsey sequence [3,50]) to convert the coherences to the populations of the m = ±1 atomic states, which could be measured by state-selective photoionization [49,50].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently suggested that metastable helium (He * ) (which can be made into a Bose-Einstein condensate [20]) is a promising candidate for atom interferometry experiments [21], for several reasons: Due to its low mass, it can be accelerated fast and efficiently, allowing fast separation of finite-size wave packets and easy detection of different momentum states. For example, helium atoms that differ by two-photon momenta separate 20 times faster than rubidium.…”
mentioning
confidence: 99%
“…Position-sensitive detectors can be used to make a full three-dimensional reconstruction of the atomic cloud [22,23] which helps to diagnose systematic effects. Another advantage of He * is its low second-order Zeeman shift of 2.3 mHz/G 2 [21] (2 times smaller than for 88 Sr and ∼10 5 times smaller than for Rb and Cs [24,25]), relaxing the required magnetic field control. For recoil measurements, an added advantage is that the mass of helium is known with a 20 times higher accuracy than that of Rb, Cs, or Sr [26,27].…”
mentioning
confidence: 99%